(untitled) (Anclajes, 2019)
Along with a collective proposal for self-assertion of a peripheral identity and style, the literature produced in São Paulo’s outlying areas from the late 90s is composed of a series of writers that show their concern regarding the construction of self-representation and their texts’ beyond the "marginal" designation, while self-identifying as part of a group. This article analyzes the legitimization and consecration mechanisms of the paulistano author Ferréz taking into account the complexity of his profile as a literary writer.